Procedural sedation and analgesia in children undergoing digestive endoscopic procedures – paediatrician or anaesthesiologist? - Bartkowska-Śniatkowska, Alicja; Rosada-Kurasińska, Jowita; Ignyś, Iwona; Grześkowiak, Małgorzata; Zielińska, Marzena; Bienert, Agnieszka (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Endoscopic procedures of the gastrointestinal tract were successfully introduced into paediatric practice in the 1970s. Recent expansive development has become useful for improvement of both diagnosis and treatment in many children with gastrointestinal diseases. Most of these procedures are performed under procedural sedation (PSA) knowing anatomical, physiological and psychological differences and requiring good experience from the paediatrician and anaesthesiologist. These principles help to provide the procedure safely and minimise adverse events, which are greater the smaller the child is. Procedural sedation and analgesia in healthy children can be performed by a paediatrician, but children with congenital defects and serious coexisting diseases (ASA ≥ III) and also during the usage of anaesthetics (e.g. propofol), should be managed by an anaesthesiologist.